Prenatal detection of major congenital heart disease – optimising resources to improve outcomes. (August 2016) - Corcoran, Siobhan; Briggs, Kaleigh; O' Connor, Hugh; Mullers, Sieglinde; Monteith, Cathy; Donnelly, Jennifer; Dicker, Patrick; Franklin, Orla; Malone, Fergal D.; Breathnach, Fionnuala M.
Abstract: Introduction: Congenital heart disease (CHD) is the most common major structural fetal abnormality and the benefits of prenatal detection are well described. The objective of this study was to evaluate the precision of prenatal diagnosis at a single tertiary referral unit over two three year periods (2006, 2007, 2008 and 2010, 2011, 2012), before and after a prenatal screening protocol for CHD was developed to include extended cardiac views, mandatory recall for suboptimal views, and a multidisciplinary Fetal Cardiac clinic was established. There exists a single national centre for paediatric cardiothoracic surgery in Ireland, a situation which facilitates near complete case ascertainment. Materials and methods: Surgery records of the National Children's Cardiac Centre were interrogated for all cases of major congenital heart defects requiring surgical intervention in the first six months of life. Minor procedures such as ligation of a patent ductus arteriosus and isolated atrial septal defect repairs were excluded. Analyses of the Fetal Medicine database at the Rotunda Hospital (a stand-alone tertiary level perinatology centre with 8500 deliveries per year) and the mortality data at the Perinatal Pathology department were conducted. The Cochrane–Armitage trend test was used to determine statistical significance in prenatal detection rates over time. Results: 51, 822 women delivered during the study period, and the incidence of major congenital heart disease either that underwent surgical intervention or that resulted in perinatal mortality, was 238/51, 822 (0.5%). Prenatal detection of major CHD increased from 31% to 91% ( p  < 0.001). Detection of critical duct-dependant lesions rose from 19% to 100%. Conclusion: We attribute the dramatic improvement in prenatal detection rates to the multifaceted changes introduced during the study period. Improved prenatal detection for births that are geographically remote from the National Paediatric Cardiac Centre will require local replication of this prenatal programme.